2021
DOI: 10.1038/s41467-021-27385-3
|View full text |Cite
|
Sign up to set email alerts
|

CRIg on liver macrophages clears pathobionts and protects against alcoholic liver disease

Abstract: Complement receptor of immunoglobulin superfamily (CRIg) is expressed on liver macrophages and directly binds complement component C3b or Gram-positive bacteria to mediate phagocytosis. CRIg plays important roles in several immune-mediated diseases, but it is not clear how its pathogen recognition and phagocytic functions maintain homeostasis and prevent disease. We previously associated cytolysin-positive Enterococcus faecalis with severity of alcohol-related liver disease. Here, we demonstrate that CRIg is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…We observed that oral phage treatment can upregulate F4/80 , a marker of resident Kupffer cells in the liver [ 25 ]. Kupffer cells play a crucial role in the phagocytosis of translocated bacteria; thus, an increased number of the first will increase the clearance of the latter [ 18 ]. An in vitro study with Staphylococcus aureus and Pseudomonas aeruginosa phages demonstrated the production of both inflammatory and anti-inflammatory cytokines from peripheral blood mononuclear cells (the prevailing effect being anti-inflammatory) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that oral phage treatment can upregulate F4/80 , a marker of resident Kupffer cells in the liver [ 25 ]. Kupffer cells play a crucial role in the phagocytosis of translocated bacteria; thus, an increased number of the first will increase the clearance of the latter [ 18 ]. An in vitro study with Staphylococcus aureus and Pseudomonas aeruginosa phages demonstrated the production of both inflammatory and anti-inflammatory cytokines from peripheral blood mononuclear cells (the prevailing effect being anti-inflammatory) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, innate immunity and the complement system have been implicated in many facets of ALD (Santiesteban‐Lores et al, 2021). While some complement factors are protective and some harmful in the pathogenesis of ALD, it seems that the induction of this pathway in E8G3 may function to protect against bacterial translocation similar to acute phase response (Cohen et al, 2010; Duan et al, 2021; Roychowdhury et al, 2009). Another pathway that changed in our analysis was oxidative phosphorylation between E8G1 and E8G3.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of IL-17 receptor might promote intestinal dysbiosis and LPS translocation into visceral adipose tissue by inhibiting the migration of neutrophils in the intestinal mucosa, leading to glucose intolerance and insulin resistance in HFD-fed mice ( Pérez et al, 2019 ). Complement receptor of the immunoglobulin superfamily (CRIg) is expressed on human macrophages and plays an important role in immune responses ( Duan et al, 2021 ). Luo et al observed an accumulation of EVs containing gut microbial DNAs and a decrease in the number of liver CRIg + macrophages in obesity ( Luo et al, 2021 ).…”
Section: Molecular Mechanisms Linking Host and The Gut Microbiota In ...mentioning
confidence: 99%